Future strategies in treatment of parkinson’s disease - Janbaz, KH; Qadir, MI; Younas, F; Malik, SA (Journal of College of Medical Sciences-Nepal, 2012)
Parkinson’s disease (PD) is a neurodegenerative disorder. COMT inhibitors, MOA-B inhibitors, Levodopa, Levodopa in combination with Dopa Decarboxylase (DDC) inhibitors, Entacapone, Tolcapone, Pramipexole, Ropinirole, Zonisamide, Cholinesterase inhibitors such as rivastigmine, galantamine and donepezil are used for treatment of Parkinson’s disease. Gene therapy of cellular and brain circuit pathways for the treatment of PD is under trials. Recently nuclear transfer embryonic stem cells or induced pluripotent stem derived cells can be used. The presence of Lewy bodies, reduced dopamine transporter and tyrosine hydroxylase expression within transplanted cells indicated that grafted cells are pathological. Adult and fetal neural stem cells are self-renewable. Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-2, 67-71 DOI: http://dx.doi.org/10.3126/jcmsn.v7i2.6687